Analisis Pengaruh Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan Platform Pembelajaran Daring terhadap Kepuasan Pengguna - Firdaus, Nur Muhammad; Ardianto, Yusaq Tomo; Sisharini, Nanik (Universitas Merdeka Malang, 2024)
In the digital age, the shift from sliding learning to online learning has become a must, which forces educational institutions and pupils to adapt to the dynamics of technology. Using the Zoom Meeting online learning system as one of the learning media, it shows how important technology is in organizing learning to be more accessible and flexible. Students can easily attend online lectures or seminars anytime and anywhere. The selection of samples is done using purposive sampling, by selecting samples based on certain criteria that are already defined, namely active students of the Master of Management at Merdeka Malang University who use the Zoom Meeting application as a platform to learn online, as many as 115 respondents. The study collected data by sending questionnaires to respondents through Google Forms. The data was analyzed through three different approaches: descriptive analysis, classical assumptions, and double linear regression. The results showed that the three variables, namely system quality, information quality, and service quality, have an impact on the satisfaction of Zoom users. Among the three, the quality of service was found to have the greatest impact on improving user satisfaction.